The dimensions of rural tourism experience: impacts on arousal, memory, and satisfaction - Kastenholz, E.; Carneiro, M. J.; Marques, C. P.; Loureiro, S. M. C. (Journal of Travel and Tourism Marketing, 2018)
Rural tourism is driven by the search for unique and memorable experiences in particular settings, but knowledge on visitors’ experiences in rural destinations is still scarce. This paper analyzes the rural tourism experience of Portuguese tourists who answered an online survey (N = 252). The paper aims at validating, in the rural tourism context, a previously proposed tourist experience scale, and analyzing the relationships between the experience, arousal, memory, and satisfaction. Results reveal that the rural tourism experience dimensions of education and esthetics positively predict rural tourists’ arousal, whereas escapism and esthetics determine memorability. Finally, implications for rural tourism marketing are discussed.